The price tag for transforming food systems under climate change: How transforming food systems under climate change will cost trillions, but inaction will cost more - Thornton, Philip K.; Chang, Yuling; Loboguerrero Rodriguez, Ana María; Campbell, Bruce M. (2022)
This brief summarises the estimated costs of implementing high-priority actions for transforming the food system, under four key action areas, as set out in the Actions to Transforming Food Systems under Climate Change report (Steiner et al. 2020): • REROUTE farming and rural livelihoods to new trajectories • DE-RISK livelihoods, farms and value chains • REDUCE emissions through diets and value chains • REALIGN policies, finance, support to social movements, and innovation